Preparation method and application of anti-fatigue dual-network composite hydrogel
The polyvinyl alcohol and pectin composite hydrogel was prepared through freeze-thawing technology to form a double network structure that resisted fatigue, solved the problem of insufficient fracture toughness and cell affinity in tissue engineering, and achieved high elasticity and cell adhesion performance. Lift, suitable for ergonomic engineering stents.
Patent Information
- Application Number
- CN202411406147.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-10
AI Technical Summary
Existing hydrogels lack ideal fracture toughness and strength in tissue engineering, and have poor cell affinity, making it difficult to use as efficient scaffolding materials.
Polyvinyl alcohol and pectin composite hydrogels were prepared through freeze-thawing process to form anti-fatigue dual network composite hydrogels, including semi-crystalline PVA polymer network and pectin calcium network, improving its mechanical properties and cell adhesion ability.
Hydrogels that achieve high elasticity, toughness and fatigue resistance can restore their initial state after significant deformation and significantly improve cell adhesion performance. They are suitable for human tissue engineering scaffolds.
Smart Images

Figure CN119286172A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of hydrogel preparation, and particularly relates to a preparation method and application of an anti-fatigue double-network composite hydrogel. Background Art
[0002] Hydrogels are three-dimensional polymer networks that contain a large amount of water (>80%) and have a structural integrity similar to that of the natural extracellular matrix (ECM). Hydrogels are considered one of the most attractive scaffold candidates for tissue engineering due to their inherent biocompatibility due to their high water content. Unfortunately, they do not exhibit the ideal fracture toughness and strength required for scaffolds used in load-bearing applications. To overcome this obstacle, efforts have been made to strengthen or enhance the mechanical properties of hydrogels, such as by incorporating inorganic nanoparticles, formulating nanostructures, or preparing composite hydrogels.
[0003] Among these efforts, composite hydrogels based on two different interpenetrating polymer networks have become a unique way to enhance the mechanical properties of hydrogels. "Jiehao Chen, Jiahe Huang, Yuhang Hu. 3D Printing of Biocompatible Shape-Memory Double Network Hydrogels. Acsami. 2012.0c17622" proposed a one-pot method for printing biocompatible shape memory DN hydrogels by fusion deposition. Two networks of polyacrylamide (PAAm) and gelatin were combined into the hydrogel ink. The PAAm network is covalently cross-linked and is responsible for the permanent shape, while the gelatin network has thermoreversible cross-linking and is responsible for fixing the temporary shape, realizing 3D printable shape memory DN hydrogels, showing higher toughness, and further research is needed to realize its application in tissue engineering.
[0004] Chinese patent CN118697942A (publication date September 27, 2024) A cartilage repair scaffold and a preparation method thereof, the cartilage repair scaffold comprising a polymer mesh scaffold, the gaps of the polymer mesh scaffold are filled with hydrogel, liposome microspheres are dispersed in the hydrogel, wherein the compression modulus of the polymer mesh scaffold is 7.5 9.5MPa. The cartilage repair scaffold has mechanical properties matching those of natural cartilage, as well as good mechanical strength and good biocompatibility. The invention still has the problem of poor cell affinity using a polymer mesh scaffold.
[0005] How to prepare a hydrogel with favorable mechanical properties, low cytotoxicity, good synthesis properties and cell adhesion gelling properties to facilitate the design and development of scaffolds for application in tissue engineering needs further study. Summary of the invention
[0006] In order to solve the above problems, the present invention prepares polyvinyl alcohol and pectin composite hydrogel by freeze-thaw process, and provides a preparation method and application of anti-fatigue double network composite hydrogel.
[0007] The invention discloses an anti-fatigue double network composite hydrogel. The composite hydrogel is composed of polyvinyl alcohol and pectin. The mass concentration of the polyvinyl alcohol and pectin in the gel is 5-15%.
[0008] Furthermore, the composite hydrogel includes two network structures, the first network is a semi-crystalline PVA polymer assembled through a cyclic freeze-thaw process, and the second network is a pectin calcium network constructed by ionic interactions between calcium and pectin.
[0009] Furthermore, the composite hydrogel is an egg-box structure, which is used to fix bioactive components or cells in the gel structure.
[0010] Furthermore, the pectin gelling process is repeatable, mainly achieved by introducing calcium ions.
[0011] A method for preparing an anti-fatigue double-network composite hydrogel comprises the following steps:
[0012] S1. Mix polyvinyl alcohol and pectin in a weight ratio of 8:1, take 5-15 g of the mixture and evenly distribute it in 100 mL of 95° C. deionized water for 2 hours;
[0013] S2, pour the mixed solution into a preheated mold, keep it at -20°C for 72 hours, and then keep it at room temperature for 1 hour;
[0014] S3, repeatedly freezing and thawing the solution obtained in step S2 twice to obtain a semi-crystalline polyvinyl alcohol polymer;
[0015] S4. The mixture is then completely immersed in a calcium chloride solution for 24 hours, and then completely immersed in deionized water until the gel reaches equilibrium swelling.
[0016] Furthermore, there is ionic crosslinking between the pectin and calcium ions, and after the pectin calcium network is formed in the semi-crystalline polyvinyl alcohol polymer through step S4, the tensile modulus and fracture toughness increase by three times.
[0017] Furthermore, the freezing time of the freeze-thaw process in step S3 is 22-23 hours, and the thawing time is 1-2 hours.
[0018] Application of a fatigue-resistant double-network composite hydrogel in the preparation of human tissue engineering scaffolds.
[0019] Compared with the prior art, the technical solution of the present application has the following advantages and effects:
[0020] 1. The fatigue-resistant double-network composite hydrogel provided in the present application is a double-network composite hydrogel constructed of a semi-crystalline polyvinyl alcohol polymer and a pectin calcium network. It has good elasticity, toughness and fatigue resistance, a tensile elongation of more than 300%, a certain degree of energy dissipation, and can serve as a buffer against external impacts.
[0021] 2. The present application provides an interpenetrating network structure consisting of a primary semi-crystalline polyvinyl alcohol network and a secondary pectin calcium physical ion network to form a mechanically strong hydrogel that can not only withstand significant deformation without breaking, but also recover to its initial state with viscoelasticity after the load is removed. The cross-link rupture is weak but reversible under applied load, and the degree of cross-link dissociation is greater in denser networks.
[0022] 3. The present application provides a method for preparing a fatigue-resistant double-network composite hydrogel, which first prepares a semi-crystalline polyvinyl alcohol polymer and then forms a pectin calcium network. Compared with a single polyvinyl alcohol hydrogel or uncross-linked pectin and calcium ions, the composite hydrogel has better mechanical properties of Young's modulus and fracture energy, and can be used to prepare human tissue engineering scaffolds.
[0023] The above is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application so that it can be implemented in accordance with the contents of the specification, and to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the following is a detailed description of the preferred embodiments of the present application in conjunction with the accompanying drawings as follows.
[0024] Based on the detailed description of the specific embodiments of the present application in combination with the accompanying drawings below, those skilled in the art will become more aware of the above and other objects, advantages and features of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can also be obtained based on these drawings without creative work. In all drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, each element or part is not necessarily drawn according to the actual scale.
[0026] Figure 1 This is a flow chart of a method for preparing an anti-fatigue double network composite hydrogel according to an embodiment of the present invention;
[0027] Figure 2 1 is a molecular structure diagram of polyvinyl alcohol and pectin according to an embodiment of the present invention, wherein Figure (a) is a molecular structure diagram of polyvinyl alcohol, and Figure (b) is a molecular structure diagram of polyvinyl alcohol;
[0028] Figure 3 1 is a graph showing the mechanical properties and adhesion ability of a composite hydrogel according to an embodiment of the present invention, wherein (a) shows the relationship between the viscoelastic behavior of the composite hydrogel and the oscillating strain, (b) shows the Young's modulus of the hydrogel under tensile and compression tests, (c) shows the stress-strain curve of the tensile performance, (d) shows the cyclic tensile test graph, and (e) shows the cyclic compression test graph;
[0029] Figure 4 1 is a characterization diagram of the composite hydrogel formed in one embodiment of the present invention, wherein Figure (a) is a Young's modulus diagram, Figure (b) is a fracture energy diagram, and Figure (c) is a stress-life behavior diagram;
[0030] Figure 5 1 is a graph of the recovery capacity of a composite hydrogel according to an embodiment of the present invention, wherein FIG. (a) is a graph of the tensile properties of the composite hydrogel scaffold, FIG. (b) is a graph of a cyclic tensile test at 100% strain, FIG. (c) is a graph of a cyclic compression test at -60% strain, and FIG. (d) is a graph of a fatigue life curve;
[0031] Figure 6 is a diagram of cell adhesion in different scaffolds according to an embodiment of the present invention, Figure 6 a is the adhesion diagram of polyvinyl alcohol hydrogel, Figure 6 b is the adhesion diagram of PVA-Pec-10 hydrogel. DETAILED DESCRIPTION
[0032] To make the purpose, technical scheme and advantages of the embodiment of the present application clearer, the technical scheme in the embodiment of the present application will be clearly and completely described below in conjunction with the drawings in the embodiment of the present application. Obviously, the described embodiment is a part of the embodiment of the present application, rather than all the embodiments. In the following description, specific details such as specific configurations and components are provided only to help fully understand the embodiments of the present application. Therefore, it should be clear to those skilled in the art that various changes and modifications can be made to the embodiments described herein without departing from the scope and spirit of the present application. In addition, for clarity and brevity, the description of known functions and structures is omitted in the embodiment. It should be understood that "one embodiment" or "this embodiment" mentioned throughout the specification means that the specific features, structures or characteristics related to the embodiment are included in at least one embodiment of the present application. Therefore, "one embodiment" or "this embodiment" appearing in various places throughout the specification may not necessarily refer to the same embodiment. In addition, these specific features, structures or characteristics can be combined in one or more embodiments in any suitable manner.
[0033] In addition, the present application may repeat reference numerals and / or letters in different examples. This repetition is for the purpose of simplicity and clarity, and does not in itself indicate the relationship between the various embodiments and / or settings discussed.
[0034] The term "and / or" in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, B exists alone, and A and B exist at the same time. The term " / and" in this article describes another type of association relationship between associated objects, indicating that there can be two relationships. For example, A / and B can mean: A exists alone, and A and B exist alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0035] It should also be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusions.
[0036] Example 1
[0037] like Figure 1 As shown, this embodiment provides a method for preparing an anti-fatigue double network composite hydrogel, according to the following steps, respectively
[0038] S1. Mix polyvinyl alcohol and pectin in a weight ratio of 8:1. Take 5 g, 10 g or 15 g of the mixture respectively and evenly distribute it in 100 mL of 95°C deionized water for 2 hours. Figure 2 (a) and (b) show the molecular structures of polyvinyl alcohol and pectin, respectively;
[0039] S2, pour the mixed solution into a preheated mold, keep it at -20°C for 72 hours, and then keep it at room temperature for 1 hour;
[0040] S3, repeating freezing and thawing twice on the solution obtained in step S2, with the freezing time being 23 hours and the thawing time being 1 hour, to obtain a semi-crystalline polyvinyl alcohol polymer;
[0041] S4, then completely immersing the mixture in a calcium chloride solution for 24 hours, and then completely immersing it in deionized water until the gel reaches equilibrium swelling. Composite hydrogels with a total amount of polymer in the solution volume of 5, 10, and 15 w / v (hereinafter referred to as: PVA-Pec-5, PVA-Pec-10, and PVA-Pec-15) were prepared.
[0042] Technical effect of this embodiment: This embodiment provides a method for preparing an anti-fatigue double-network composite hydrogel, which can prepare composite hydrogels with different total amounts of polymers in the solution volume.
[0043] Example 2
[0044] Based on the composite hydrogels with different total amounts of polymer in the solution volume in Example 1, the relationship between the viscoelastic behavior (storage modulus and loss modulus) and the oscillation strain of the composite hydrogels with a total amount of polymer of 5, 10, and 15 w / v in the solution volume was detected by rheological experiments under oscillation mode. Figure 3 a. At low oscillatory strain (<0.1%), a linear viscoelastic (LVE) region is observed, where the storage modulus (G′) and loss modulus (G″) are relatively constant. Hydrogels with higher polymer concentrations show higher G'. As the oscillatory strain increases, G' begins to decrease, while G″ begins to increase, indicating that the polymer network is deformed. After the transition point (G′=G″ or Tanδ=1), the hydrogel transitions from a solid state (G′>G″) to a liquid state (G′>G″). <G〃)。
[0045] In addition to the viscoelastic behavior, the tensile and compressive properties of the swollen hydrogels were investigated at body temperature (37°C). All three hydrogels were elastic and tough, and their tensile elongation reached more than 300% ( Figure 3 c). The Young's modulus of the hydrogel increases with the increase of polymer concentration, which is in good agreement with the results of viscoelastic behavior. The Young's modulus of PVA-Pec-15 reaches 117.9±9.0 kPa in the tensile test and 79.3±20.6 kPa in the compression test ( Figure 3 b).
[0046] The stress-strain curve of the hydrogel under cyclic loading is shown in Figure 3 d and e. The curves show that all three hydrogels can recover to their original shape even after 100% stretching or 50% compression. The hysteresis loop observed after unloading reveals the viscoelastic nature of the materials, which may be caused by the weak but reversible breakage of cross-links under the applied load. The degree of hysteresis increases with increasing polymer concentration, indicating a greater degree of cross-link dissociation in denser networks.
[0047] Technical effect of this embodiment: This embodiment verifies that the composite hydrogel is a mechanical response system, and its rheological properties fluctuate with changes in stress or strain. It also has viscoelastic behavior, good tensile and compressive properties, and the cross-linking properties of the composite hydrogel related to viscoelasticity are weak but reversible.
[0048] Example 3
[0049] This example further verifies the cross-linking performance and anti-fatigue ability of the PVA-Pec-5, PVA-Pec-10, and PVA-Pec-15 composite hydrogels described in the above examples.
[0050] After adding calcium pectin network to polyvinyl alcohol hydrogel, the tensile modulus (~30±20 kPa to ~100±10 kPa) and fracture toughness (~300±100 Jm-2 to ~900±100 Jm-1) increased by about three times, and the tensile modulus and fracture toughness were as follows Figure 4 (a)(b) The addition of uncrosslinked pectin (PVA-Pec-no Ca2+) or Ca2+ ions (PVA-Ca) alone had a positive effect on the mechanical properties of the PVA hydrogel system, including Young's modulus and fracture energy. However, the greatest improvement was observed in the PVA-Pec hydrogel with an ionically crosslinked calcium-pectin network. The stress-lifetime behavior of the PVA hydrogel and composite hydrogel is shown in Figure 4 (c) as shown.
[0051] The composite hydrogel exhibited recovery ability over more than 5 cycles, and the energy dissipation and the appearance of hysteresis loops were observed as Figure 5 (a) shows the tensile properties of different PVA-Pec scaffolds, (b) is a cyclic tensile test at 100% strain, (c) is a cyclic compression test at -60% strain, and (d) is a fatigue life curve.
[0052] Technical effect of this embodiment: This embodiment verifies that the cross-linked calcium-pectin network has a significant improvement on the Young's modulus and fracture energy of the composite hydrogel, and has good recovery ability.
[0053] Example 4
[0054] This embodiment relates to the use of the fatigue-resistant double-network composite hydrogel described in the above embodiment in the preparation of human tissue engineering scaffolds. The preparation process includes placing the gel at the bottom of a confocal dish, adding 1×10 4 After incubation for 12 hours, the adherent cells were fixed and cell microfilaments and nuclei were stained. Images were collected using a confocal microscope. Figure 6 Cell adhesion diagram in different scaffolds, Figure 6 a Polyvinyl alcohol hydrogel adhesion diagram, Figure 6 bPVA-Pec-10 hydrogel adhesion diagram, it can be seen that the adhesion in PVA-Pec-10 hydrogel is more than that in polyvinyl alcohol hydrogel.
[0055] Technical effect of this embodiment: This embodiment verifies that the composite hydrogel has good cell adhesion performance and can be used in human tissue engineering scaffolds.
[0056] The above description is only the preferred embodiment of the present invention, which does not limit the protection scope of the present invention. For those skilled in the art, the present invention can be modified and varied in various ways. Within the spirit and principle of the present invention, any change, modification, replacement, integration and parameter change of these embodiments by conventional substitution or capable of achieving the same function without departing from the principle and spirit of the present invention shall fall within the protection scope of the present invention.
Claims
1. An anti-fatigue double network composite hydrogel, characterized in that: The composite hydrogel consists of polyvinyl alcohol and pectin, and the mass concentration of the polyvinyl alcohol and pectin in the gel is 5-15%.
2. The anti-fatigue double network composite hydrogel according to claim 1, characterized in that: It includes two network constructions, the first network is a semi-crystalline PVA polymer assembled through a cyclic freeze-thaw process, and the second network is a pectin-calcium network constructed by the ionic interaction between calcium and pectin.
3. The anti-fatigue double network composite hydrogel according to claim 1 or 2, characterized in that: The composite hydrogel is an egg-box structure and is used to fix bioactive components or cells in the gel structure.
4. The anti-fatigue double network composite hydrogel according to claim 1 or 2, characterized in that: The pectin gelation process is made reproducible by introducing calcium ions.
5. A method for preparing an anti-fatigue double network composite hydrogel according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Mix polyvinyl alcohol and pectin in a weight ratio of 8:1, take 5-15 g of the mixture and evenly distribute it in 100 mL of 95°C deionized water for 2 hours; S2, pour the mixed solution into a preheated mold, keep it at -20°C for 72 hours, and then keep it at room temperature for 1 hour; S3, repeatedly freezing and thawing the solution obtained in step S2 twice to obtain a semi-crystalline polyvinyl alcohol polymer; S4. The mixture is then completely immersed in a calcium chloride solution for 24 hours, and then completely immersed in deionized water until the gel reaches equilibrium swelling.
6. The method for preparing the fatigue-resistant double-network composite hydrogel according to claim 5, characterized in that: There is ionic crosslinking between the pectin and calcium ions. After the pectin calcium network is formed in the semi-crystalline polyvinyl alcohol polymer through step S4, the tensile modulus and fracture toughness increase by three times.
7. The method for preparing the fatigue-resistant double network composite hydrogel according to claim 5, characterized in that: The freezing time of the freeze-thaw process in step S3 is 22-23 hours, and the thawing time is 1-2 hours.
8. Use of the fatigue-resistant double-network composite hydrogel according to any one of claims 1 to 7 in preparing a human tissue engineering scaffold.
Citation Information
Patent Citations
Cartilage repair scaffold and preparation method thereof
CN118697942A
Fructus ligustri lucidi polysaccharide-polyvinyl alcohol-pectin hydrogel with antibacterial and anti-inflammatory activity as well as preparation method and application thereof
CN118085480A
Polyvinyl alcohol-based interpenetrating type gel
JP2019085521A